Approaches to psychocorrection of cognitive disorders in people who have suffered ischemic stroke - Drozdova, Iryna (Psychosomatic Medicine and General Practice, 2025)
In approaches to psychocorrection of patients after a stroke, it is necessary to take into account the personality of patients, the stages of the process, adherence to treatment, individuality, a combination of influences, and continuity. The Aim. Assess the effectiveness of the program of psychocorrection of cognitive disorders in people who have suffered an ischemic stroke. Materials and methods. On the basis of the State Institution "UD SRI MSPI MZH of Ukraine" 83 patients with stage III hypertension were examined. with the consequences of cerebral stroke, who were divided into two clusters (cluster I – 40 people with mild (MilCI) and cluster II – 43 people with moderate (ModCI) cognitive impairments. Results. As a result of combined treatment, long-term memory in people with MilCI and ModCI significantly improved – by 19,4 and 49,0%, figurative – by 12,9 and 50,7%, visual – by 22,0 and 31,5%, substantive – by 18,0 and 37,0% and the volume of short-term memory – by 19,7 and 22,9%. Memorization and short-term memory also improved; in both groups, memorization of the first test increased – by 12,9 and 19,1%, the second test – by 5,8 and 20,3%, the third test – by 6,5 and 26,3%, the fourth sample – by 2,3 and 30,1% and short-term memory – by 5,6 and 19,7%. Selective attention in patients with MilCI and ModCI probably increased by 36,8 and 47,8% and the level of logical thinking – by 12,8 and 23,7% and improved work efficiency – by 13,7 and 17,0%. Conclusions. We have developed a model of psychocorrection based on methodology (body-oriented and psychophysiological approaches); principles of complexity, differentiation, systematicity, stages and sequence; components (informational, emotional and behavioral); levels (internal and interpersonal and social); targets (psychological and cognitive disorders, limitations of vital activity); Art therapy methods (drawing and coloring, dance and music therapy, fairy tale therapy) can be widely use